Vitamin D Receptor in Muscle Atrophy of Elderly Patients: A Key Element of Osteoporosis-Sarcopenia Connection - Scimeca, Manuel (Aging Dis, 2018)
In this study, we investigated the relationship between sarcopenia (evaluated in term of fibers atrophy), vitamin d receptor protein expression and TaqI/Cdx2/FokI VDR genotypes in an Italian cohort of osteoporosis(n=44) and osteoarthritis (n=55) patients. Muscle biopsies were fixed and investigated by both immunohistochemistry (vitamin d receptor expression) and transmission electron microscopy (satellite stem cells niches). Vitamin d receptor polymorphisms were studied on DNA extracted from muscle paraffin sections. For the first time, we reported that aging differently affects the VDR activation in OA and OP patients. In particular, while in OP patients we observed a significant reduction of VDR positive myonuclei with age, no “age effect” was observed in OA patients. The frequent activation of VDR could explain the lower number of atrophic fiber that we observed in OA patients respect to OP. From genetic point of view, we showed a putative association among polymorphisms FokI and Cdx2 of VDR gene, vitamin d receptor activation and the occurrence of sarcopenia. Altogether these data open new prospective for the prevention and cure of age-related muscle disorders.